Finite element modelling of a magma chamber surrounded by country-rock, with particular reference to the groundwater flow in sections of different permeability - Remsing, Carmen (Rhodes University, Faculty of Science, Department of Physics, 2003)
This thesis presents results of two-dimensional finite element modelling of a magma chamber surrounded by country-rock containing a section of high permeability. The high permeability section in the country-rock simulates structure that is predominant in controlling the groundwater convection pattern and resulting mineral deposits. The models have analogies in nature: for instance the gold mines in the Massif Central of France, the Pogo mine in Alaska and the Pilgrim's Rest gold field in South Africa. This is a complicated coupled system involving fluid flow and heat transfer under extreme conditions. The magma in the chamber convects and as it cools the heat liberated causes convection in the groundwater contained in the surrounding country-rock. This convection in turn affects the rate of liberation of heat from the magma. The software used for the modelling, FLOTRAN, is the computational fluid dynamics component of the commercial ANSYS package. The results obtained describe in detail the flow pattern in the magma chamber, the country-rock and high permeability section thereof. During the cooling of the magma chamber the groundwater convects more vigorously in the high permeability section than elsewhere, and a convection cell is seen forming within this region. This provides a mechanism for hydrothermal formation of valuable mineral deposits in the structure near a magma chamber. It is found that the relationship between the velocity of the flow in the cell and the temperature of the magma chamber is well represented by a first order linear differential equation, providing a simple understanding of this process,,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Magmas; Groundwater flow